The universalization of Physical Culture in Yateras 2003-2014 - Alain Castaño-Torres (Cultura Física y Deportes de Guantánamo, 2018)
This investigation exposes the process of universalization of the Physical Culture in Yateras municipality, in the period of 203-2014. The universe is formed by 197 students and 6 professors. Different variables are studied, such as: Principals of branch, chief structure, local, communications technology, entrance roads, the professors' educational and scientific category, as well as the quantity of graduate. Scientific methods of the theoretical and empiric level were used as: historical-logical, analytic-synthetic, interviews, bibliographical revision, iconography and charts. It was possible to incorporate to the egregious to the performance spheres, being increased the systematic practitioner in the six Popular Council.